Pengaruh Penggunaan Teknologi, Leadership dan Spiritualitas terhadap Keberhasilan Bisnis UMKM Desa Waru Lor Wiradesa - Sofiana, Rizky Ekawati; Abadi, Muhammad Taufiq (Journal of Business & Applied Management, 2023)
Business success is not synonymous with how much success a person has in making a profit so as to make him a rich man, but it is seen from whether or not a person is able to form, establish and run a business that was previously small and familiar in the community and then can develop, be recognized and accepted by the community. The purpose of this study is to determine the factors that influence the success of MSME businesses including the use of technology, leadership and spirituality. This research approach uses quantitative methods. While the research design is a causal design that functions to determine the effect of one variable on another. The population in this study were all Batik MSMEs in Warulor Village, Wiradesa District, Pekalongan, totaling 100. The analysis technique used multiple linear regression with the help of Microsoft Excel and SPSS version 23. The results showed that the use of technology and leadership had a significant influence on the success of MSME businesses. While the spirituality variable does not have a significant influence on the success of MSME businesses. Simultaneously, the use of technology, leadership and spirituality has a significant effect on the success of MSME businesses